Pengaruh Earning Per Share (EPS) Dan Price Earning Ratio (PER) Terhadap Harga Saham Pada Pt Unilever Indonesia Tbk Periode 2013-2023 - Lola Tri Lestari; Fikron Al-Choir (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study is to determine the effect of Earning Per Share (EPS) and Price Earning Ratio (PER) on stock prices of PT Unilever Indonesia Tbk for the period 2013–2023. The research method used is quantitative with a multiple linear regression approach. Based on the partial test results (t-test), the Earning Per Share (EPS) variable obtained a t-count value of 2.459 with a significance value of 0.039. Since t-count > t-table (2.459 > 2.306) and the significance value (0.039 < 0.05), it can be concluded that Earning Per Share has a significant effect on stock prices. For the Price Earning Ratio (PER) variable, the t-count value is 3.522, which is greater than the t-table value of 2.306, and the significance value is (0.008 < 0.05). This indicates that Price Earning Ratio has a significant effect on stock prices. The results of the simultaneous hypothesis test (F-test) show that F-count > F-table (9.059 > 8.020) and the significance value is (0.009 < 0.05). Therefore, it can be concluded that Earning Per Share and Price Earning Ratio simultaneously have a significant effect on stock prices. Furthermore, the coefficient of determination) is 0.617 or 61.7%